Medication Errors: Realities and Perspectives - Štuhec, Matej (Anali PAZU, 2022)
A medication error (ME) is an unintended failure in the pharmacotherapy process that leads (or potential) significant harm to the patient. Each year in the U.S., serious preventable ME occur in 3.8 million inpatient admissions and 3.3 million outpatient visits, whereas inpatient preventable ME cost $16.4 billion annually and outpatient $4.2 billion, which represents 7,000 deaths in the U.S. each year are due to preventable ME. Although this serious important topic has been discussed recently, a burden and costs of this problem in Slovenia remains unknown. Numerous strategies to prevent from ME exist, including an inclusion of clinical pharmacists next to the patients' beds. In this review, an overview of this topic is discussed.
Keywords: medical errors; adverse event; literature review; treatment failure and costs; clinical pharmacy